THE ROLE OF THE ACCOUNTANT IN THE ADAPTATION OF ORGANIC PRODUCTION TO EU REQUIREMENTS - MARKEVYCH, Liudmyla; BEZDUSHNA, Yuliia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The growth of demand for organic products on the world food markets determines the development of organic production in Ukraine. However, in order to enter international markets, in particular the European one, producers of organic products must comply with a number of requirements regarding their quality and certification. The purpose of the article is to generalize the requirements for organic production in the EU countries and to justify the role of the accountant and accounting policy of the enterprise in the process of adapting the activities of producers of organic products in Ukraine to such requirements. Achieving the planned goal was carried out with the help of analytical, synthetic, tabular, graphic methods, etc. The article summarizes the relevance of the export orientation of domestic production with a statistical selection of the most exported crops of organic plant production. An assessment of the formation of the necessary level of preparation for export trade was carried out, with a list of preparatory actions being highlighted. The main documents regulating the production and export of organic products in the EU countries are indicated. The algorithm of processes during the export of organic products from Ukraine in accordance with the requirements of the European Commission regarding additional official measures to control the import of organic products is summarized. The article proves the important role of the accountant in these processes and proposes a system of registers of accounting and control of the production of organic agricultural products, taking into account the requirements and standards of the EU. The proposed document registration system will contribute to the systematization of information about the quality of organic crop production, and will allow the recording of certification procedures at each stage of production.
Keywords: accounting profession; crop production; organic products; accounting; accounting registers; production costs